Green Synthesis Ag Nanopartikel Berbasis Moringa Oleifera untuk Meningkatkan Absorbansi Pewarna Organik D205 pada Elektroda ZnO Nanorod - Nurhamidah, Millah; Pujiarti, Herlin; Ma'arifah, Alfiatul; Diningsih, Ridha (Universitas Sultan Ageng Tirtayasa, 2025)
Green synthesis of AgNPs using Moringa Oleifera extract has many advantages, including low toxicity, relatively low cost, environmentally friendly materials, and the availability of easily obtainable materials. AgNPs also have the advantage of enhancing light absorption in the visible region due to the occurrence of an optical phenomenon known as Localized Surface Plasmon Resonance (LSPR). In this study, AgNPs were composited with the organic dye D205 to examine the effect of AgNPs composites on the increased absorbance of the organic dye D205 on ZnO nanorod electrodes and its influence on the material's band gap. The method used in this research is the green synthesis of AgNPs by reducing Moringa Oleifera extract with the reducer AgNO3, which produces AgNPs powder. Then, in this study, ZnO nanorod electrodes were synthesized using the hydrothermal method. After that, the ZnO nanorod electrode was immersed with the organic dye D205, which was composited with AgNPs. The variation in this study lies in the variation of AgNPs composites at 0 wt% and 10 wt%. Sample characterization was performed using XRD, SEM, and UV-Vis. This study shows that the crystal size of AgNPs is 34 nm, and the maximum diffraction peak is at 2θ = 32.16˚ on the hkl (122) plane. The SEM results show an average diameter of AgNPs of 85 nm, with EDX indicating an atomic weight of Ag compound of 79%. The absorbance values in this study from the variations of AgNPs composites and organic dyes at 0 wt% and 10 wt% were 321 nm and 325 nm, respectively. The Band gap values of the AgNPs and organic dye composite variations at 0 wt% and 10 wt% are 3.69 eV and 2.99 eV, respectively. The research results show that the AgNPs composite with the organic dye D205 successfully increased absorbance and reduced the material's band gap by about 0.7 eV. Thus, the AgNPs composite with the organic dye D205 has the potential to improve efficiency in ZnO nanorod-based DSSC applications.